Novel injectable calcium phosphate scaffold with human periodontal ligament stem cell encapsulation in microbeads for bone regeneration - Qiu, Gengtao; Huang, Mingguang; Ke, Difeng; Liu, Jin; Weir, Michael D.; Ma, Tao; Wang, Ping; Oates, Thomas W.; Schneider, Abraham; Xia, Yang; Xu, Hockin H. K.; Zhao, Liang (Frontiers in Materials, 2022)
Objectives: (1) Develop a novel construct of human periodontal ligament stem cells (hPDLSCs) encapsulated in degradable alginate microbeads (DAMB) with human platelet lysate (hPL) and injectable calcium phosphate cement (ICPC); (2) Investigate the proliferation and osteogenic differentiation of hPDLSCs in ICPC with hPL as a xeno-free supplement and animal serum replacement for bone tissue engineering applications. Methods: hPDLSCs were encapsulated in alginate-fibrin microbeads (DAMB+fibrin), alginate-hPL degradable microbeads (DAMB+hPL), or alginate-fibrin-hPL microbeads (DAMB+fibrin+hPL). The proliferation and osteogenic differentiation of hPDLSCs were investigated in culturing with the ICPC scaffold. Results: Flexural strength of ICPC was 8.4 ± 0.91 MPa, and elastic modulus was 1.56 ± 0.1 GPa, exceeding those of cancellous bone. hPDLSCs had higher viability in DAMB+fibrin+hPL group than in DAMB+fibrin. ALP was 69.97 ± 16.96 mU/mg for ICPC+DAMB+fibrin+hPL group, higher than 30.68 ± 2.86 mU/mg of ICPC+ DAMB+fibrin (p<0.05) and 4.12 ± 1.65 mU/mg of control (p<0.01). At 7 days, osteogenic gene expressions (ALP, RUNX2, COL1, and OPN) in ICPC+ DAMB+fibrin+hPL and ICPC+DAMB+fibrin were 4-11 folds that of control. At 21 days, the hPDLSC-synthesized bone mineral amounts in ICPC+DAMB+fibrin+hPL and ICPC+DAMB+fibrin were 13.2 folds and 11.1 folds that of control group, respectively. Conclusions: The novel injectable CPC scaffold encapsulating hPDLSCs and hPL is promising to protect and deliver hPDLSCs. The hPL-based medium significantly enhanced the osteogenic differentiation of hPDLSCs in ICPC+DAMB+fibrin+hPL construct, suggesting a promising xeno-free approach for bone tissue regeneration applications.